Current status and development trends of deep coalbed methane research in China - Wei JU; Shu TAO; Zhaobiao YANG; Jiayao CHENG; Haiyan SHANG; Weike NING; Chunlong WU (Shiyou shiyan dizhi)
Deep coalbed methane (CBM) possesses enormous resource potential and is essential for increasing unconventional natural gas reserves and production on a large scale in China. To understand the current status of CBM research and development in China, systematic retrieval and classification of deep CBM-related publications are conducted using the China National Knowledge Infrastructure (CNKI) database and Wanfang Data Knowledge Service Platform. Based on this analysis, the status of deep CBM research in China is reviewed, and its development trends are discussed, providing insights into adaptive exploration and development technologies for deep CBM. The results indicate that the temporal distribution of publications reflects the evolution of China's deep CBM research and industrial development, which can be divided into four stages: the initial exploration stage (1994 to 2005), the slow development stage (2006 to 2015), the steady progress stage (2016 to 2020), and the rapid development stage (since 2021). Geological and engineering "dual sweet spot" prediction is a key research focus for deep CBM research. Conducting geology and engineering integrated research for deep CBM exploration and development, based on the quantitative characterization of geological and engineering parameters and using three-dimensional geological and geomechanical modeling, is a critical pathway to ensuring profitable development. The production state and development degree of natural fractures in coal reservoirs significantly affect fracturing transformation. The connectivity of fracture networks before and after fracturing is an important indicator for determining the performance of deep CBM development. The development of deep CBM technologies and their applicability are the key areas to be explored in the future. Deepening theoretical understanding, quantitatively characterizing geological and engineering conditions, and comprehensively analyzing influencing factors are fundamental and crucial for the further rapid development of deep CBM in China. Deep and ultra-deep CBM in basins such as the Ordos, Junggar, Sichuan, and Tarim basins will be the research focus and the key exploration and development areas.